3m+n-9m+3n=

Simple and best practice solution for 3m+n-9m+3n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+n-9m+3n= equation:


Simplifying
3m + n + -9m + 3n = 0

Reorder the terms:
3m + -9m + n + 3n = 0

Combine like terms: 3m + -9m = -6m
-6m + n + 3n = 0

Combine like terms: n + 3n = 4n
-6m + 4n = 0

Solving
-6m + 4n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4n' to each side of the equation.
-6m + 4n + -4n = 0 + -4n

Combine like terms: 4n + -4n = 0
-6m + 0 = 0 + -4n
-6m = 0 + -4n
Remove the zero:
-6m = -4n

Divide each side by '-6'.
m = 0.6666666667n

Simplifying
m = 0.6666666667n

See similar equations:

| p-32=6(18-7) | | 120-5x=2x+15 | | -40=-5p | | 14-10x=23-17x | | 16x-278=6x-8 | | 2(x-1)=10 | | -47-3x=13-9x | | -5+17=6b-1-5b | | -8=p-13 | | 8+5(d-1)-6(d-3)=3(4-d) | | 5x-2(0)=10 | | -13+8= | | 16-(p+2)=3(p-7)+10 | | 4(0)-5y=60 | | 7x=30+40 | | 20+8(3c-2)=(c-1)+3(2c-4) | | 4x+8=57-3x | | -114-9x=10x+19 | | 4x-5y=60 | | Y=-x^2+5x+11 | | 117-3x=15x+21 | | 5x+8=107-6x | | -4x=19+9 | | 5(2x+3)=6(x+2)-2(x-4) | | Y=x^2+5x+11 | | 0=2(b-2)-3(3b+1) | | 6x+1=12-5x | | (x^2+3x+2.25)-2.25=0 | | 0=2(3a-5)-5 | | x-3+2x+1= | | 3x+x=36 | | 79y-20+8=3(y-4)-2 |

Equations solver categories